Heart rate reduction as a marker to optimize carvedilol treatment and enhance myocardial recovery in pediatric dilated cardiomyopathy - Adorisio, Rachele; Pontrelli, Giuseppe; Cantarutti, Nicoletta; Bellettini, Elisa; Caiazza, Martina; Mencarelli, Erica; Limongelli, Giuseppe; Poli, Daniela; Drago, Fabrizio; Kirk, Richard; Amodeo, Antonio (Frontiers in Physiology, 2022)
Introduction: An elevated heart rate is associated with an increased risk of death or cardiac transplant in children with dilated cardiomyopathy (DCM). Whether heart rate is a clinical marker to address therapy, is poorly investigated in children. Aim: To investigate the relationship between heart rate reduction (HRR) and left ventricular ejection fraction (LVEF) in DCM, treated with carvedilol. Methods: This is a multi center retrospective analysis conducted on all children with DCM (aged < 18 years) between 2013 and 2020, with LVEF < 40% and treated with carvedilol. Carvedilol was up titrated to the maximal tolerated dose or to 1 mg/kg/day. Echocardiographic data on left ventricular function and dimension were collected. The relationship between HRR and LVEF, left ventricular end-diastolic (LVEDd) and end-systolic diameter (LVESd) was assessed before and after HRR with carvedilol, using regression analysis. Results: 100 patients were enrolled (M: 51%; age 7 ± 8 y). The mean LVEF was 30.2 ± 10% before treatment and 43.7 ± 9.6% after treatment, at the maximum therapeutic dose (p < 0.0001). There was a positive relationship between HRR and increase in LVEF (R2 =0.06, p=0.014). A HRR of > 20% correlated with an improvement in LVEF > 13%. At 3 years follow up, HRR demonstrated a significant reduction of LVESd (R2=0.1, p=0.003) LVEDd (R2 =0.07, p=0.008) and LVEF recovery up to 15% (p<0.0001). No deaths or heart transplant occurred during follow-up. Conclusions: This study demonstrates that HRR is safe and improvement in LVEF is related to the degree of HRR. The magnitude of LVEF improvement was enhanced by a major reduction in HR. It provides evidence that HRR could be used as a clinical marker to treat HF in children.